Stocktaking of Global Forced Displacement Data - Sarzin, Zara (World Bank, Washington, DC, 2017)
Conflict-induced forced displacement is receiving increased interest within the international community. However, establishing an accurate picture of its scale and dynamics is extremely challenging. Large amounts of data on forced displacement are collected and disseminated each year and used to inform policy and programming by humanitarian and development actors. However, not all of these data are credible or complete, and there are significant gaps in the data required for longer-term development planning. This paper reviews the various sources of data on forced displacement and assesses how these can be improved to enable more effective analysis and assistance by development actors. At an aggregate level, the headline figure of 65 million forcibly displaced persons is an estimate, and the data on internally displaced persons are the least robust. There are also several significant gaps in data collection for those populations that are of concern to development actors, especially returnees, as well the substantial number of people living in displacement-affected host communities. In addition, there is little comprehensive data available on the socioeconomic vulnerabilities and needs of displaced populations, or on the social and economic impacts of displacement on host countries and communities. Significant efforts are needed to enhance the reliability, comparability, quality, and scope of data on forced displacement in general, and address the gaps in the data required for long-term development planning.